PMP certification : a beginner's guide - Angel, George G. (University Press of Colorado, 2022)
"This fourth edition provides up-to-date information on how to effectively manage projects, programs, and portfolios. It includes new content at the end of each chapter and a mock exam to help prepare readers for the PMI certification exams to prepare the reader to become a certified PMP or CAPM" --